2004
DOI: 10.1111/j.1432-1033.2004.04271.x
|View full text |Cite
|
Sign up to set email alerts
|

Cdt1 and geminin are down‐regulated upon cell cycle exit and are over‐expressed in cancer‐derived cell lines

Abstract: Licensing origins for replication upon completion of mitosis ensures genomic stability in cycling cells. Cdt1 was recently discovered as an essential licensing factor, which is inhibited by geminin. Over-expression of Cdt1 was shown to predispose cells for malignant transformation. We show here that Cdt1 is down-regulated at both the protein and RNA level when primary human fibroblasts exit the cell cycle into G0, and its expression is induced as cells re-enter the cell cycle, prior to S phase onset. Cdt1's in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
108
1
30

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(149 citation statements)
references
References 37 publications
10
108
1
30
Order By: Relevance
“…A second vector for in situ hybridization was generated by subcloning the mIdas open reading frame to pBluescript between SacI and KpnI sites. The following plasmids have been described elsewhere: GemininGFP (29), Geminin⌬90 -120GFP (30,31), Cdt1dhcRed (31), GemininHA (29), plasmids for mouse Geminin in situ probes (32,33).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A second vector for in situ hybridization was generated by subcloning the mIdas open reading frame to pBluescript between SacI and KpnI sites. The following plasmids have been described elsewhere: GemininGFP (29), Geminin⌬90 -120GFP (30,31), Cdt1dhcRed (31), GemininHA (29), plasmids for mouse Geminin in situ probes (32,33).…”
Section: Methodsmentioning
confidence: 99%
“…For control sense probe generation, the pBluescript vector containing the mIdas open reading frame was linearized with KpnI and transcribed with T7 RNA polymerase. Geminin sense and antisense probes were as described previously (32,33). Sense probes were used as the control in all experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From these observations, it was believed that geminin likely would have tumorsuppressive functions. However, previous reports have demonstrated that the expression of geminin rises with increasing tumor grade, [11][12][13][14][15][16] leading to a poor prognosis in a variety of cancer patients, eg, breast cancer and renal cell carcinoma. 17,18 Thus there has been a discrepancy between normal molecular function and the outcomes of clinical studies of geminin in many cancers.…”
mentioning
confidence: 99%
“…Immunohistochemistry and immunoblotting for geminin revealed that, except in testis, where its expression is high, this protein is absent in organs with minimal proliferation activity (heart, nerves, prostate, kidney, lung and scheletric muscle) and it is specifically expressed in proliferating lymphocytes, male germ cells and epithelial cells. [55][56][57] Interestingly, geminin is frequently overexpressed in human primary colon, rectal and breast tumors, in a subset of non-small-cell lung carcinomas, in B-cell lymphoma and in cancer cell lines of different histogenic origin and its upregulation correlated with high proliferative activity of tumor cells, [58][59][60][61][62] suggesting that this protein could exhibit oncogenic activity. Although being initially proposed as a tumor suppressor gene, geminin does not appear to exert an antiproliferative effect in these tumors but its role is supportive to consider geminin as a marker of proliferation.…”
Section: Who Does Control Geminin Transcription?mentioning
confidence: 99%